2002
DOI: 10.1034/j.1600-0749.2002.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Spleen and Liver Pigmented Macrophages of Rana Esculenta L. A New Melanogenic System?

Abstract: The present study reports the results of a morpho-functional analysis of spleen pigmented cells from Rana esculenta L. and comparison with liver melanin-synthesizing cells, belonging to the macrophage cell lineage. Cytological and cytochemical analyses show that parenchymal pigmented cells of the spleen, like those of the liver, are positive to peroxidase and lipase reactions and have phagocytic properties. The observation of premelanosomes in various stages of differentiation, together with the demonstration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
50
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 45 publications
14
50
0
1
Order By: Relevance
“…Melanomacrophages are rounded (Sichel et al, 1997) and contain the catabolic substances hemosiderin and lipofuscin (Agius, 1981;Agius and Roberts, 2003). Both types of internal pigment cells have cytoprotective functions against free radicals (Mcgraw, 2005), produce melanin (Gallone et al, 2002(Gallone et al, , 2007 and detoxify pollutants (Fenoglio et al, 2005) in addition to functions related to the immune system (Franco-Belussi et al, 2013) and pathologies (Roberts, 1975). There is evidence that melanin participates in innate immunity and regulates cytokine activity (Mackintosh, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanomacrophages are rounded (Sichel et al, 1997) and contain the catabolic substances hemosiderin and lipofuscin (Agius, 1981;Agius and Roberts, 2003). Both types of internal pigment cells have cytoprotective functions against free radicals (Mcgraw, 2005), produce melanin (Gallone et al, 2002(Gallone et al, , 2007 and detoxify pollutants (Fenoglio et al, 2005) in addition to functions related to the immune system (Franco-Belussi et al, 2013) and pathologies (Roberts, 1975). There is evidence that melanin participates in innate immunity and regulates cytokine activity (Mackintosh, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Fish and amphibians have pigmented cells called visceral melanocytes and melanomacrophages in internal organs and membranes (Gallone et al, 2002;Franco-Belussi et al, 2011Nilsson Sköld et al, 2013). Visceral melanocytes are in many ways similar to skin melanocytes (Zuasti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Aggregations of pigmented cells, termed MMs, have been found in the livers of some fishes [8,9], amphibians [10][11][12][13], and reptiles [14][15][16][17]. Previous studies demonstrated that the pigmented cells of amphibian livers are cells belonging to the macrophage lineage of Kupffer cells [23][24][25] as well as the MMs centers of fishes [19,26,27].…”
Section: Distribution Of Mms In the Livermentioning
confidence: 99%
“…In heterothermic vertebrates, aggregations of pigmented cells termed melanomacrophages (MMs) have been identified in the livers of some fishes [8,9], amphibians [10][11][12][13], and reptiles [14][15][16][17]. Extracutaneous melanin-containing cells have been detected in various tissues and organs such as the liver, spleen, kidney, and lungs [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Ectothermic vertebrates have a well-developed system of melanin-containing cells, distributed among several organs (liver, spleen, lung, heart, thymus, and gonads) and tissues (meninges and connective tissues surrounding blood vessels) composing an extracutaneous pigmentary system (Gallone et al, 2002).…”
mentioning
confidence: 99%